Remote Detection of a Freshwater Pool Off the Sagavanirktok River Delta, Alaska - Kovacs, A.; Morey, R.M. (ARCTIC, 1979)
. This field study has shown how an impulse radar ice profiling survey can be used to survey for fresh water in isolated pools under the ice cover of arctic river deltas. .